2012
DOI: 10.3892/mmr.2012.1220
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fatty acid synthase suppresses osteosarcoma cell invasion and migration via downregulation of the PI3K/Akt signaling pathway in vitro

Abstract: In the present study, the effect of fatty acid synthase (FASN) inhibition on cell invasion and migration in vitro was investigated. A recombinant plasmid containing a microRNA targeting the FASN gene was used to inhibit FASN expression in U2‑OS cells. Cell migration and invasion were investigated using wound healing and Transwell invasion assays. We found that cell invasion and migration were suppressed by inhibiting FASN. In addition, the effect of inhibition of FASN on phosphorylation of Akt was investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 38 publications
5
20
0
1
Order By: Relevance
“…A B OS cells. These findings are also concordant with those of previous studies, which indicated that the PI3K/Akt pathway has a critical role in cancer chemoresistance (22)(23)(24)(25). Of note, the selective PI3K inhibitor only blocked ~50% of the effect of PCX on cisplatin chemoresistance and cell survival in OS cells, suggesting the involvement of other signaling pathways, which may be identified in further studies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A B OS cells. These findings are also concordant with those of previous studies, which indicated that the PI3K/Akt pathway has a critical role in cancer chemoresistance (22)(23)(24)(25). Of note, the selective PI3K inhibitor only blocked ~50% of the effect of PCX on cisplatin chemoresistance and cell survival in OS cells, suggesting the involvement of other signaling pathways, which may be identified in further studies.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have demonstrated that the PI3K/Akt pathway is important for cancer cell chemoresistance (22)(23)(24)(25). Therefore, the present study examined the effects of PCX on the activity of PI3K and phosphorylation of Akt in OS cells.…”
Section: Effects Of Pcx On Pi3k Activity and Phosphorylation Of Akt Imentioning
confidence: 99%
“…The protective effect of ischemic pretreatment on the myocardium is predominantly due to the activation of the PI3K/Akt signal transduction pathway (22). Efthymiou et al (23) identified that administering atorvastatin reduced the myocardial infarction area (MI) in the ischemia reperfusion model of the normal myocardium of rats in vitro.…”
Section: B Amentioning
confidence: 99%
“…It was also determined that the migratory ability of OECs was governed by the expression of migrationrelated factors, such as MMPs and NCAM1. MMP-2 and MMP-9 play important roles in the migration and invasion of various cells, 24) including OECs. 25,26) Secreted MMPs regulate the activity of the membrane, which is important for both cell migration and axonal regeneration.…”
Section: Discussionmentioning
confidence: 99%